Placa microcontrolada para controle supervisório com interface web - Jabs, Darney (2015)
This work presents the development of a microcontrolled device with the TCP/IP protocol embedded able to connect to the Internet to control processes and provide data for supervision in real time able to communicate with the users through a web interface. The microcontrolled board, based on the PIC18F4620 microcontroller and TCP/IP protocol embedded, offering for the user versatility and low cost. The development of the web pages is done in HTML and CSS codes with JavaScript functions. As an application example, it was designed a microcontrolled printed-circuit board with digital functions of inputs and outputs, pulse-width modulation (PWM) and digital/analog conversion controlled by a web page.